The Urgency of Law Enforcement Relating to Criminal Acts of Sexual Violence in Public Transportation Mode - Lintang Ayu Saraswati; Bambang Waluyo (Dinasti Research, 2025)
The objective of this paper is to inspect the lawful prosecution of sexual assault in public tr?nsport?tion and the application of the Sexual Violence Offenses Act to prosecute sexual assault in public tr?nsport?tion. The form of research is executed using normative juridical by applying the method of statutory and legal conceptual approach. The result reveals the enforcement of sexual assault law in the public transportation could be implemented by using the Criminal Code and the Sexual Violence Offenses Act. Nevertheless, the Sexual Violence Offenses Act will be able provide legal protection and eliminate the feeling of inequality experienced by victims of sexual assault inside the public transportation mode.